The Nagoya University and the University of Adelaide Joint PhD Degree Program in Medicine – A Program of Opportunity - Aleksić, Branko; Arthur, Agnieszka; Kasai-Prince, Mika; Chrétien, Basile; Bustos‐Villalobos, Itzel; Plewa, Carolin; Kasuya, Hideki; Page, Amanda; Zannettino, Andrew C.W.; Kimura, Hiroshi (Advances in Medical Education and Practice, 2025)
The Joint PhD Degree Program (JDP) between Nagoya University (NU) and the University of Adelaide (UoA), launched in 2015, was the first such initiative of its type in Japan. Evolving from a student exchange, it required the Japanese Ministry of Education, Culture, Sports, Science and Technology (MEXT) accreditation and alignment of differing PhD admission criteria. Challenges included degree naming and eligibility requirements, which NU and UoA addressed through mutual recognition agreements. Since inception, the JDP has maintained steady enrolment, with doctoral degree students engaging in joint research and publishing over 30 peer-reviewed articles. Future developments include postdoctoral pathways and industry internships, reinforcing the Program's role in fostering and enhancing global medical research collaboration.